The UK vertical lift network and the mentor project - Dehaeze, F. (My University, 2021)
The UK Vertical Lift Network (UK VLN), founded in 2013, aims at developing synergies between its members and promote collaboration within the UK rotorcraft research community. It is doing so by facilitating the involvement of other members of the network in new research projects. The network is also encouraging cooperation in educational and training activities, through the organisation of yearly events. The VLN collaboration lead to the start of the MENtOR project (Methods and Experiments for NOvel Rotorcraft), which proposes to develop new methods to predict and analyse tiltrotor aircraft, using a multi-disciplinary approach linking aerodynamics, dynamics, control algorithms and flight simulation. The project aims at delivering a set of tools and methods to all members able to perform comprehensive analyses of tiltrotor aircraft.